2022
DOI: 10.3390/biology11060874
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of MRAP2 Protein Sequence Generates a Functional Novel Pharmacological Modulator for MC4R Signaling

Abstract: As a member of the melanocortin receptor family, melanocortin 4 receptor (MC4R) plays a critical role in regulating energy homeostasis and feeding behavior, and has been proven as a promising therapeutic target for treating severe obesity syndrome. Numerous studies have demonstrated that central MC4R signaling is significantly affected by melanocortin receptor accessory protein 2 (MRAP2) in humans, mice and zebrafish. MRAP2 proteins exist as parallel or antiparallel dimers on the plasma membrane, but the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…While the inversion of the N-terminal, C-terminal, or transmembrane regions of MRAP2 did not affect dimer formation, it altered the pharmacological regulation of MC4R signaling ( Wang et al, 2021 ). And we also demonstrated that the complete reversion of the whole MRAP2 protein sequence could generate a functional novel pharmacological modulator of MC4R ( Xu et al, 2022 ).…”
Section: Characterization and Physiological Functions Of The Mrap Familymentioning
confidence: 83%
“…While the inversion of the N-terminal, C-terminal, or transmembrane regions of MRAP2 did not affect dimer formation, it altered the pharmacological regulation of MC4R signaling ( Wang et al, 2021 ). And we also demonstrated that the complete reversion of the whole MRAP2 protein sequence could generate a functional novel pharmacological modulator of MC4R ( Xu et al, 2022 ).…”
Section: Characterization and Physiological Functions Of The Mrap Familymentioning
confidence: 83%
“…Similar to the study by Motegi et al, 29 specific deletion of the MC4R gene in VGlut2 neurons caused obesity in mice. Early studies using MC4R KO mice, or MC4R agonists, 30 showed that MC4R regulates food intake independently of changes in body weight. Xu et al 27 reported a significant reduction in energy expenditure in MC4R‐deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Melanocortin 2 receptor accessory protein 2 (MRAP2) is a regulatory protein that is expressed in the HEK-293 cells we used [52], but not in COS-7 cells [53]. Several studies have shown that MC4R signaling is highly affected by MRAP2 [54][55][56][57][58]; therefore, the presence or rather, in the case of COS-7 cells, the absence of MRAP2 can affect results. Furthermore, the SV40 promoter used for our MC4R expression plasmids is ideal for COS-7 cells [59] but results in reduced expression in HEK-293 cells, which is wanted in our study to better resemble the physiological state.…”
Section: Discussionmentioning
confidence: 99%